Etiological factors related to denture stomatitis: A meta-analysis - Alberto Rodriguez-Archilla; Carolina Garcia-Galan (Wolters Kluwer Medknow Publications, 2020)
Denture stomatitis (DS) is a very common disorder that affects upper denture wearers. Clinically, DS presents erythema and inflammation of the palatal mucosa covered by the denture. The objective of the study was to assess the etiological factors related to DS. A search for articles on etiological factors related to DS was performed in the following electronic databases: PubMed (MEDLINE, Cochrane Library), Web of Science (WoS), and Spanish Medical Index (IME). One thousand five hundred thirty-two articles were found (683 in PubMed, 829 in WoS, and 19 in IME), 340 of them were duplicates. From 330 articles with full-text availability, 306 were excluded for several reasons. Finally, 24 studies were included in this meta-analysis. For dichotomous outcomes, the estimates of effects of an intervention were expressed as odds ratios (ORs) using Mantel-Haenszel method with 95% confidence intervals. Data were processed using the statistical software RevMan 5.3. The most important risk factors for DS were Candida species infection (OR: 5.64,P < 0.001), denture age over 10 years (OR: 5.36, P = 0.02), the existence of denture trauma related to ill-fitting denture (OR: 4.30, P = 0.02), night sleeping with the denture (OR: 4.09,P < 0.001), poor denture cleaning (OR: 2.81, P = 0.02), high carbohydrate intake (OR: 1.83, P = 0.01), and female gender (OR: 1.42, P = 0.02). The most common microorganisms in DS were the Candida albicans fungus and the Stafilococcus aureus bacteria. Infection by species of the genus Candida seems to be the main etiological factor of DS.